Analisis Perbandingan Potensi Financial Distress Dengan Metode Altman Z-Score Dan Springate Pada PT. Kediri Tani Sejahtera Sebelum Dan Saat Pandemi Covid-19 - Violy Amanda Salsabilla; Marhaendra Kusuma; Rike Selviasari (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This research aims to analyze the application of the Altman Z-Score method and the Springate method to predict financial distress at PT Kediri Tani Sejahtera and aims to analyze the comparison of financial distress from the Altman Z-Score and Springate methods before and during the Covid-19 pandemic for the 2018-2022 period. The type of this research is quantitative descriptive research, using the Altman Z-Score and Springate methods. The results of the research show that the Springate model is a reliable model for anticipating possible financial difficulties in businesses based on the two models that have been studied, while the Altman Z-Score model shows that corporations are in a gray state or experienced some minor financial difficulties during 2018-2022.